Tinjauan Kritis Terhadap Konsep Agama Sebagai Institusi Sosial dalam Ide Moderasi di Indonesia - Kristeno, Marianus Rago; Derung, Teresia Noiman (Institut Agama Kristen Negeri Palangka Raya, 2024)
Religion has an important role in the lives of Indonesian society as a social institution that functions to maintain social stability. Amidst the diversity of cultures, languages, traditions and religions, conflict and intolerance often arise as challenges to the role of religion in society. Conflict situations that occur due to differences in religious views or understanding often become obstacles to carrying out the role of religion as a social institution. This research aims to examine the concept of religious moderation as an effort to overcome social conflict and discrimination in relation to the role of religion as a social institution. Using qualitative descriptive methods and literature study techniques, this research analyzes themes related to religious moderation and the role of religion from various literary sources so that conclusions can be drawn regarding the role of religion which tries to carry out its function through religious moderation in Indonesia. The research results show that although religion, which is a community belief system, has a significant role in instilling social values, rigid traditional views often hinder inclusiveness and tolerance. This traditional view hinders the implementation of religious moderation which aims to create social harmony, so that religion as a social institution cannot carry out its role. Therefore, the concept of religious moderation needs to be developed as an implementation of the role of religion so that society can live in peace.